2019
DOI: 10.1186/s12906-019-2573-x
|View full text |Cite
|
Sign up to set email alerts
|

Safety assessment of the ethanolic extract of Gongronema latifolium Benth. leaves: a 90-day oral toxicity study in Sprague Dawley rats

Abstract: Background The leaves of Gongronema latifolium Benth. have long been recognized traditionally as a remedy for a variety of ailments in Africa. This study was conducted to evaluate the safety profile of the ethanolic extract of G. latifolium (GLES) leaves through a repeated dose 90-day oral toxicity study in male and female of Sprague Dawley rats. Methods GLES was orally administered at doses of 250, 500 and 1000 mg/k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…GLB has been used as antidiabetic spice and vegetable in traditional folk medicine in the southern parts of Nigeria and other parts of Africa [10]. Besides, the leaves are incorporated into a tea blend that is mainly marketed to diabetes mellitus patients in the United States [16,17]. Several in vivo studies have helped to provide support for the ethnopharmacological use of GLB against hyperglycaemia, obesity, and diabetes [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…GLB has been used as antidiabetic spice and vegetable in traditional folk medicine in the southern parts of Nigeria and other parts of Africa [10]. Besides, the leaves are incorporated into a tea blend that is mainly marketed to diabetes mellitus patients in the United States [16,17]. Several in vivo studies have helped to provide support for the ethnopharmacological use of GLB against hyperglycaemia, obesity, and diabetes [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Towards the phytochemical and biological characterization of GLB which may further support its nutritional and ethnopharmacological use in humans, several classes of phytochemicals such as: pregnanes, phytosterols, anthraquinones, and essential oils have been identified [20,[26][27][28]. Such phytochemicals, which are characterized by large-scale structures, are known to possess high efficiency and ability to bind to multifarious targets [29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Hypertrophy of the hepatic tissues was evident in the experimental rat groups administered with comparatively high doses of PE and EA fractions of O. gratissimum leaf extract. Specifically, the increase in liverbody weight ratio of the experimental rat groups administered with PE and EA fractions of O. gratissimum leaf extract was an indication of hepatocellular hypertrophy, inflammation and fibrosis, with resultant hepatic dysfunction as previously described 15,55 . Empirical investigations showed that hepatic hypertrophy is primarily the manifestation of accumulation of lipids as well as other connecting pathologic factors 55 .…”
Section: Discussionmentioning
confidence: 62%
“…Elevations of plasma low threshold substances in the blood are indicative of compromised renal function. The kidney function test (KFT) measures plasma creatinine and blood urea nitrogen (BUN) levels, among other blood indicators, such that their raised levels in the blood are diagnostic of presentation and progression of renal disease 15 . The renal/kidney function test indicators are applied in monitoring the efficacy of therapeutic intervention against compromised renal function 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Sprague-Dawley (SD) rats have been widely used to study toxicities of medicinal herbs [13]. In the present study, in order to provide guidance for the clinical use of HS, we tested the 24-week oral dosing toxicities of HS in SD rats.…”
Section: Introductionmentioning
confidence: 99%